2023
DOI: 10.15663/wje.v28i1.1063
|View full text |Cite
|
Sign up to set email alerts
|

STEM teacher professional development in pre-service teacher education: A literature review

Abstract: Science, technology, engineering, and mathematics (STEM) education has recently been gaining popularity in a number of countries. This seems to have ramifications for increasing the intensity with which professional development programmes are implemented at both in-service and pre-service teacher levels. The present study provides a systematic literature review on scientific articles published between 2015 and 2021, examining how STEM teacher professional development programmes (STEM-TPD) led in the pre-servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
(101 reference statements)
0
2
0
1
Order By: Relevance
“…The study results showed that the solar panel project can be an engaging learning context for students. This finding gives us an insight that using projects closely related to contemporary global issues, such as the energy crisis, not only increases students' engagement but also deepens their understanding of the real applications of STEM concepts (Struyf et al, 2019;Suryadi et al, 2023). According to the literature, choosing interdisciplinary and challenging learning contexts can influence students' motivation (El Nagdi & Roehrig, 2020;Mayasari et al, 2019).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The study results showed that the solar panel project can be an engaging learning context for students. This finding gives us an insight that using projects closely related to contemporary global issues, such as the energy crisis, not only increases students' engagement but also deepens their understanding of the real applications of STEM concepts (Struyf et al, 2019;Suryadi et al, 2023). According to the literature, choosing interdisciplinary and challenging learning contexts can influence students' motivation (El Nagdi & Roehrig, 2020;Mayasari et al, 2019).…”
Section: Discussionmentioning
confidence: 89%
“…Although the Ministry of Education has provided guidebooks, many teachers still experience difficulties implementing integrated STEM learning (Muchtar & Ding, 2024;Nuragnia et al, 2021). Suryadi et al (2023) showed that efforts to develop teacher professionalism in integrated STEM teaching in Indonesia are relatively scarce. Furthermore, Sulaeman et al (2022) found that the majority of Indonesian physics teachers are familiar with the integrated STEM education approach; however, more than half have never tried to implement an integrated STEM teaching approach in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Sistematis mengikuti pedoman yang ditentukan pada PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) (Abbasi et al, 2022;Mastan et al, 2022;Suryadi et al, 2023). Penelitian ini menganut prinsip analisis konten, yang difokuskan pada temuan dari berbagai penelitian yang telah dipublikasikan di jurnal ilmiah di Internasional.…”
Section: Metodeunclassified